TINGKAT KEBUGARAN JASMANI ANGGOTA UKM FUTSAL UNIVERSITAS TEKNOKRAT INDONESIA - Muhammad Vani Aprilianto; Eko Bagus Fahrizqi (Universitas Teknokrat Indonesia, 2020)
Sports Activity is related to achievements that is inseparable from some factors and one of them is physical fitness. Following the physical fitness by the members of Futsal Club Universitas Teknokrat Indonesia is unknown. This research aims to reveal the level of physical fitness of the members of Futsal Student Activity Universitas Teknokrat Indonesia, with 29 members involved. The data collecting technique uses the instrument of TKJI that consists of 5 tests that are: 50 meters Running Test, Push Up, Sit Up, Vertical Jump, Run 1.2 Kilometers, the data analyzing technique of this research uses the descriptive statistics analysis with percentage. The result shows that the level of physical fitness of Futsal Club Universitas Teknokrat Indonesia, 5 students (17,24%) classified as good, 20 students (68,96%) classified as average, 4 students (13,79%) classified as deficient, and there are no students that classified great and awful. Hence, the result of the physical fitness level test towards the members of Futsal Club Universitas Teknokrat Indonesia can be classified as average.Kata Kunci: Physical Fitness, Test , Run, Push Up, Sit Up, Vertical Jump